PERANCANGAN MODEL STRATEGIS TRANSFORMASI BISNIS RADIO LOKAL BERBASIS AI-DRIVEN TECHNOPRENEURSHIP PADA NIRWANA FM BANJARMASIN - Novia Purnamasari; Eddy Soeryanto Soeogoto; Rahma Wahdiniwaty; Irfan Dwiguna Sumitra; Adam Mukharil Bachtiar (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
The rapid development of Artificial Intelligence (AI) offers strategic opportunities to strengthen technopreneurship models, including within conventional offline businesses. This study aims to design an AI-driven strategic transformation model for a local radio business, focusing on Nirwana FM Banjarmasin, particularly its Event Organizer (EO) services, product sales, and marketing collaborations. A qualitative case study approach was employed, with data collected through in-depth interviews, field observations, and analysis of operational documents to map the existing level of technological integration. The findings reveal a significant digitalization gap, where Nirwana FM has not yet implemented AI in a comprehensive and integrated manner. Operational processes within the EO unit and marketing strategies remain largely manual and rely on fragmented technological tools. To address this issue, the study proposes a strategic AI-based model through the integration of five core solutions: (1) AI-Based Audience Analytics, (2) Predictive Analytics for Product Stock Planning, (3) AI-Powered Social Media Performance Tracking, (4) AI-Assisted Scheduling and Event Management, and (5) Automated Chatbot and Information Services. This model serves not only as an operational optimization framework but also as a sustainable hybrid business transformation strategy for local radio enterprises and MSMEs in the digital era.